Editors’ Foreword - van Rensburg, Julian Jansen; Munt, Harry; Starkey, Janet (Proceedings of the Seminar for Arabian Studies, 2017)
The Seminar for Arabian Studies is the principal international academic forum for research on the Arabian Peninsula. First convened in 1968, it is the only annual academic event for the study of the Arabian Peninsula that brings together researchers from all over the world to present and discuss current fieldwork and the latest research. The Seminar covers an extensive range of diverse subjects that include anthropology, archaeology, architecture, art, epigraphy, ethnography, history, language, linguistics, literature, numismatics, theology, and more besides, from the earliest times to the present day or, in the fields of political and social history, to around the end of the Ottoman Empire (1922).